Green energy to sustainability : strategies for global industries - Vertès, Alain A.; Qureshi, Nasib; Blaschek, Hans P.; Yukawa, Hideaki (John Wiley & Sons, Inc., 2020)
"This book is an extensive update and sequel to the successful 2010 book Biomass to Biofuels: Strategies for Global Industries, with an expanded focus on the next generation of energy technologies. Significant progress has been made in this field in the interim, and global market conditions have changed dramatically, impacting the development and feasibility of many green technologies. Focusing on the key challenges that still impede the realization of the billion-ton renewable fuels vision, Green Energy to Sustainability integrates scientific, technological and business development perspectives to highlight the key developments that are necessary for the global replacement of fossil fuels with green energy solutions. The book reviews the latest advances in biofuel manufacturing technologies in light of business, financial, value chain and supply chain concerns, discusses the deployment of other renewable energy for transportation, for example solar energy, and proposes a view of the challenges for the next 2-5 decades. The coming of age of electric vehicles is also discussed, as well as the impact of their deployment on the biomass to biofuels value chain. The book primarily aims at providing an interface useful to business and scientific managers. Emphasis has been placed throughout the book to provide a global view, reviewing deployment and green energy technology in different countries across Africa, Asia, South America, the EU and the USA"--